An Objective Study of Customer Behaviour in BPL Mobile Cellular Ltd - Francis Sudhakar, K.; Nutan, Lydia (Indian Journal of Marketing, 2005)
Life Insurance is a contract for payment of a sum of money to the person assured (or failing him/her to the person entitled to receive the sum.) on the happening of the event insured against. Usually the contract provides for the payment of an account on the date of maturity or at specified dates at periodic intervals or at an unfortunate death, if it occurs earlier. Among other things, the contract also provides for the payment of premium periodically to the corporation by the assured. Life insurance is universally acknowledged to be an institution, which eliminates ’risk’ It certainly substitutes for uncertainty and comes to the timely aid of the family in the unfortunate event of death of the breadwinner. By and large, life insurance is civilizations’ partial solution to the problems caused by death.